THE EFFECT OF COCONUT WATER ON DYSMINORRE PAIN IN ADOLESCENTS - Nabillah Pattiiha (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2021)
Introduction: Dysmenorrhea pain is an imbalance of the hormone progesterone in blood resulting in abdominal pain caused by uterine muscle spasms. coconut water contains growth hormones, magnesium and calcium which can reduce muscle tension and vitamin C which is a natural anti-inflammatory substance that can help relieve pain due to menstrual cramps. Method: Quasi-experimental research design with Non-randomized one group pretest and posttest design. It aims to determine the effect before and after administration of green coconut water to dysmenorrhea pain. Sampling using proposive sampling technique with 30 respondents. Results: Statistical test with data analysis using Shapiro-Wilk and Wilcoxon with significance (p <0.05) and significant value of 0.000 Pvalue, thus Ho was rejected. Conclusions and Recommendations: There is an effect of giving green coconut water to dysmenorrhea pain in adolescents, researchers suggest that adolescents who experience menstrual pain to consume green young coconut water on menstruation the first day.